Representações sociais da infância indócil: análise dos registros nos livros de ocorrência em uma escola municipal de Santa Maria/RS - Luft, Sibila (2012)
The current thesis of Doctorate aims to know, to analyze and to understand how are produced the social representations of unruly school children from the registers in the occurrence books of the early years of a municipal school of Santa Maria/RS. It was developed in the Line of Research Special Education of the Program of Post-Graduation in Education of the Educational Center of the UFSM/RS (PPGE/CE/UFSM). As the category childhood is a social construction, we presented a new historical view of representation, constitution and production of an unruly childhood: criminal , transgressor, disrupted and medicated childhood, upon the look of the media, the Juridical Sciences, Medical Sciences, Education and Special Education, contemplating knowledge at the level of interdisciplinarity (JAPIASSÚ, 1976) going by the construction of world landmarks in the recognizing of the rights of the children and of the Public Politics turned to these: To know the social representations (MOSCOVICI, 1978; 2010; JODELET, 2001) produced in the school space about the unruly school children, from the analysis of occurrence books and identifying procedures adapted by the school in relation to the unruly childhood demand, as well as what impacts in the practice of (in) exclusion, we contemplated questions How the representations from the analysis of book occurrences produce the exclusion of unruly students? The research was of documental nature and it involved materials that didn´t receive an analytical treatment yet (GIL, 2008, p. 66), it occurred in a municipal school of the Elementary School in the city of Santa Maria/RS with the use of 5 books of registers of occurrences involving students of the early years with total samples of 954 registers, and among them 743 (seven hundred and forty-three) of them were used in the research. The analysis and the collect of material, approved by the Ethic Committee in Research/UFSM, upon the number 0287.0.243.000-11/2011, the analysis and the collect of the material occurred in the months of June to July, 2011, and it was used diary of field and photocopy. Results evidenced that, in the context of the researched reality, questions involving the unruly childhood are of behavior level in detriment of cognitive questions. We did not evidence cases in which both the aspects were present in the registers, what implicates a displacement and a new representation formed: nowadays those demands leave the scene with problems of learning, as well as the disturbed, hyperactive and medicated students being these productions of medicine, to give place to unruly students who probably will promote the juridical instances, with that already produced in the transgressor childhood observed by the lights of the media, which comes systematically divulging and diffusing newspaper reports about the transgressor childhood, related to the appearance and explosion of a phenomenon of international level, the Bullying. The lack of specific Public Politics for education and permanence of the unruly childhood at school is of great urgency, which are added to the discussions upon the formation of teachers, due to fact that school still uses punishing, menacing and exclusive methods and techniques, what shows the unpreparedness for the work of this public. Other aspect which deserve to be evidenced involves interdisciplinary approaches, being this thematic in question crucial for the investment in the field of Public Politics in Education, contributing so for the permanence of these demands at school, minimizing impacts of exclusion still presents.